A 30-Year-Old Carrier of Gaucher Disease with Multiple Myeloma. (13th February 2019) - Chadha, Juskaran; Sahai, Tanmay; Schwimmer, Joshua; Shani, Dana
Abstract : We are reporting a case of a 30-year-old male with no past medical history who presented with new onset of renal failure, anemia, and splenomegaly and was diagnosed with multiple myeloma. Given the splenomegaly and the patient's Jewish heritage, blood tests were done and the patient was found to be a Gaucher disease carrier. The association of Gaucher disease and multiple myeloma has previously been reported; however, we want to describe the case of a young Gaucher disease carrier who developed multiple myeloma and provide a review of the literature.